EIT based on virtual instrument - Ma Jun; Wang Wenglong; Zhang Jianguo (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Design of a electrical impedance tomography system based on virtual instrument, the author firstly introduced the virtual instrument into the electrical impedance imaging from the perspective of hardware and software. The system use DAQ of NI to simplify the hardware structure and improve the stability. Software of system combines the advantages of LABVIEW and MATLAB, and verify some algorithms. Using NI virtual instrument, the system has strong expansion and do good basis for enhancing the performance of electrical impedance imaging system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2319